Respons Perkecambahan dan Pertumbuhan Bibit Tomat (Solanum lycopersicum) dalam Beberapa Media Kultur In Vitro - Riansyah, M. Afdal; Sulistiani, Rini; Hisham, Nazrul (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2026)
Tomatoes (Solanum lycopersicum L.) are an important horticultural crop with steadily increasing demand in Indonesia, yet their productivity often fluctuates. The availability of high-quality seeds, including those produced through in vitro propagation techniques, is a key factor in producing vigorous and uniform seedlings. The study employed a factorial Complete Randomized Design with two treatments. The aimed to compare the germination and early growth responses of two tomato varieties, MicroTom and MT3, on six different culture media: Full-MS, Half-MS, Full-MS+GA₃ 0.5 mg/L, Chu’s N6, Chu’s N6+GA₃ 0.5 mg/L, and Gamborg B5. The results showed that the culture medium had a significant effect on all parameters, while the variety had a significant effect only on the average germination time and shoot length. The Half-MS, Chu’s N6, and Gamborg B5 media yielded the highest germination rates (70–72%), while Full-MS produced the lowest rate (35%). MT3 exhibited a faster germination rate (6.91 days) and longer shoot length (34.41 mm) compared to MicroTom. The longest root length was observed in the MT3 grown on Half-MS (C2M2), and the longest shoot length was observed in the MT3 grown on Gamborg B5 (C2M6). GA₃ supplementation did not always enhance vigor or early growth. The interaction between variety and medium had a significant effect, particularly on root and shoot growth. This indicates that the effectiveness of the medium depends on the genotype used. Overall, Half-MS, Chu’s N6, and Gamborg B5 are recommended as optimal media for tomato germination and early growth, particularly for the MT3.